Analisis Efektivitas Metode Economic Order Quantity (EOQ) dalam Pengendalian Persediaan Sparepart Service Unit Excavator - Sechar Nurul Fadillah; Surojo, Surojo (Jurnal Teknologi dan Rekayasa Alat Berat, 2024)
Inventory management is a crucial aspect of company operations, particularly in the context of heavy equipment service unit services. This research aims to evaluate the effectiveness of the Economic Order Quantity (EOQ) method in controlling the inventory of spare parts for the XCMG XE490DK excavator service unit at PT Multi Usaha Tambang. With a focus on implementing EOQ on several sample spare parts, such as Oil Engine Gulf Super Duty Vle 15W-40 CL-4, Oil Filter LF9080, Fuel Filter/Water Separator FS19763, and Fuel Filter FS1000, this research found significant results. The research results indicate that the application of the EOQ method at PT. Multi Usaha Tambang is able to determine the optimal order quantity, optimal order frequency, optimal safety stock, and optimal reorder point for each spare part sample. More importantly, the EOQ method has been proven to be significantly more advantageous, with its ability to save inventory costs by up to 92.10%. These findings contribute positively to the operational efficiency and profitability of PT. Multi Usaha Tambang. The implementation of this research highlights the importance of applying the EOQ method in managing spare parts inventory, especially for the XCMG XE490DK excavator unit. This study provides a strong basis to recommend the EOQ method as an effective approach in optimizing inventory control and substantial cost savings.